Expression of TRAIL and TRAIL receptors in normal and malignant tissues. - Daniels, R; Turley, H; Kimberley, F; Liu, X; Mongkolsapaya, J; Ch'En, P; Xu, X; Jin, B; Pezzella, F; Screaton, G (2005)
TRAIL, tumor necrosis factor-related apoptosis-inducing ligand, is a member of the TNF family of proteins. Tumour cells were initially found to have increased sensitivity to TRAIL compared with normal cells, raising hopes that TRAIL would prove useful as an anti-tumor agent. The production of reliable monoclonal antibodies against TRAIL and its receptors that can stain fixed specimens will allow a thorough analysis of their expression on normal and malignant tissues. Here we report the generation of monoclonal antibodies against TRAIL and its four membrane-bound receptors (TR1-4), which have been used to stain a range of normal and malignant cells, as routinely fixed specimens. Low levels of TRAIL expression were found to be limited mostly to smooth muscle in lung and spleen as well as glial cells in the cerebellum and follicular cells in the thyroid. Expression of the TRAIL decoy receptors (TR3 and 4) was not as widespread as indicated by Northern blotting, suggesting that they may be less important for the control of TRAIL cytotoxicity than previously thought. TR1 and TR2 expression increases significantly in a number of malignant tissues, but in some common malignancies their expression was low, or patchy, which may limit the therapeutic role of TRAIL. Taken together, we have a panel of monoclonal antibodies that will allow a better assessment of the normal role of TRAIL and allow assessment of biopsy material, possibly allowing the identification of tumors that may be amenable to TRAIL therapy.